2022
DOI: 10.3389/fgene.2022.789573
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide SNP Analysis of Hybrid Clariid Fish Reflects the Existence of Polygenic Sex-Determination in the Lineage

Abstract: The African catfish (Clarias gariepinus) may exhibit the co-existence of XX/XY and ZZ/ZW sex-determination systems (SDSs). However, the SDS of African catfish might be influenced by a polygenic sex-determination (PSD) system, comprising multiple independently segregating sex “switch” loci to determine sex within a species. Here, we aimed to detect the existence of PSD using hybrid. The hybrid produced by crossing male African catfish with female bighead catfish (C. macrocephalus, XX/XY) is a good animal model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Perhaps, it is simply the combination of multiple and independent “switch” loci or alleles specifying the segregation of sex within a species, known as polygenic sex determination (PSD). PSD can occur by modifying current sex chromosomes to generate a third functional sex chromosome at the same locus, or by modifying autosomal loci in other regions of the genome to generate a novel process for gonad development regulation [ 16 , 17 , 18 , 109 ], resulting in the generation of multiple phenotypic or reproductive types within one sex. Such multiple classes may promote fitness benefits for natural selection in the population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Perhaps, it is simply the combination of multiple and independent “switch” loci or alleles specifying the segregation of sex within a species, known as polygenic sex determination (PSD). PSD can occur by modifying current sex chromosomes to generate a third functional sex chromosome at the same locus, or by modifying autosomal loci in other regions of the genome to generate a novel process for gonad development regulation [ 16 , 17 , 18 , 109 ], resulting in the generation of multiple phenotypic or reproductive types within one sex. Such multiple classes may promote fitness benefits for natural selection in the population.…”
Section: Discussionmentioning
confidence: 99%
“…However, this information was derived from the analysis of only one commercial stock [ 14 ]. Teleosts with different geological populations, ecotypes, or varieties are reported to have different SDSs and/or sex determination regions (SDRs) [ 15 , 16 , 17 , 18 ]. Studies on more Siamese fighting fish populations are required to confirm this.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the African catfish is considered an excellent biological model for studying amphibious traits (i.e., bimodal breathing) and terrestrial transition [16][17][18] . However, current genomics research has primarily focused on phylogenetic and domestication studies 9,[19][20][21] , as well as on sex-chromosome and karyotype evolution utilizing only a limited panel of molecular markers [22][23][24] .Clarias gariepinus genome is made up of 2n = 2x = 56 chromosomes (18 m + 20 sm + 18 st/a) 25 with a fundamental number (NF) of 94. Its chromosome system has historically been contentious.…”
mentioning
confidence: 99%
“…Previous findings suggested a XX/XY male heterogametic chromosomal system [26][27][28][29] , while others pointed to a ZZ/ZW female heterogametic sex determination system (SDS) 30,31 . However, recent research using high-throughput sequencing data have shown that both systems coexist in C.gariepinus 22,23 . The coexistence of both SDSs is most likely heavily influenced by environmental and social factors, as well as geographical habitat: the ZZ/ZW system is indicated in African wild ecotypes 25,30 , XX/XY system is observed in some anthropogenically introduced populations in Europe and China 27,28,32 , and both systems were evidenced within the same population in Thailand 22,33 .…”
mentioning
confidence: 99%